Application of Unified Theory of Acceptance, Use of Technology Model and Delone & Mclean Success Model to Analyze Use Behavior in Mobile Commerce Applications - Pramudito, Dendy K; Nuryana, Arief; Assery, Syeh; Purnomo, Hery; Ady Bakri, Asri (Jurnal Informasi dan Teknologi, 2023)
In order to assist businesses, create more efficient solutions and get the greatest benefits from these applications, this research was undertaken with the primary goal of identifying the elements that influence the behavior of utilizing food service applications and enhancing their use. Three variables from the Delone & Mclean IS Success Model and the measurement model, UTAUT, are used in this study's quantitative methodology. Users of food service applications on the island of Java make up the study's population. A total of 150 people responded to the samples. Purposive sampling was used to collect samples. Data analysis using SmartPLS version 4 and the PLS-SEM methodology. Five of the seven factors examined in the study of interest and usage behavior were found to be valid. This means that the use of food service applications can improve performance, assisted by supporting facilities and systems of good quality, so that it can affect the level of user acceptance of the food service application. This research can provide startups with an understanding of the factors that influence their application usage behavior, with the aim of increasing the acceptance and use of food service applications.